A Prospective Study of the Serological, Clinical, and Epidemiological Features of a SARS-CoV-2 Positive Pediatric Cohort - Ignacio Callejas-Caballero; Alba Ruedas-López; Arantxa Berzosa-Sánchez; Marta Illán-Ramos; Belén Joyanes-Abancens; Andrés Bodas-Pinedo; Sara Guillén-Martín; Beatriz Soto-Sánchez; Isabel García-Bermejo; David Molina-Arana; Juan-Ignacio Alós; Elvira Baos-Muñoz; et al. (MDPI AG, 2022)
Background: SARS-CoV-2 was a global pandemic. Children develop a mild disease and may have a different rate of seroconversion compared to adults. The objective was to determine the number of seronegative patients in a pediatric cohort. We also reviewed the clinical-epidemiological features associated with seroconversion. Methods: A multicenter prospective observational study during September-November 2020, of COVID-19, confirmed by reverse transcription-polymerase chain reaction. Data were obtained 4-8 weeks after diagnosis. Blood samples were collected to investigate the humoral response, using three different serological methods. Results: A total of 111 patients were included (98 symptomatic), 8 were admitted to hospital, none required an Intensive Care Unit visit. Median age: 88 months (IQR: 24-149). Median time between diagnosis and serological test: 37 days (IQR: 34-44). A total of 19 patients were non-seroconverters when using three serological techniques (17.1%; 95% CI: 10.6-25.4); most were aged 2-10 years (35%, p < 0.05). Univariate analysis yielded a lower rate of seroconversion when COVID-19 confirmation was not present amongst household contacts (51.7%; p < 0.05). Conclusions: There was a high proportion of non-seroconverters. This is more commonly encountered in childhood than in adults. Most seronegative patients were in the group aged 2-10 years, and when COVID-19 was not documented in household contacts. Most developed a mild disease. Frequently, children were not the index case within the family.